SYNTHESIS OF THE TWO DEGREES-OF-FREEDOM CONTROLLER FOR STABILIZING SYSTEM OF INFORMATION-MEASURING DEVICES - Сущенко, О. (Proceedings of National Aviation University, 2012)
The paper is devoted to the design problem of the stabilizing system of the information-measuring devices which are used for exploitation on the ground vehicles. The possibility of the two degrees-of-freedom controller H¥ -synthesis is studied in this article. This approach allows to provide the high quality both the stabilization processes and the command signals tracking processes. The main phases of the design procedure of the two degrees-of-freedom H¥ -controller for stabilizing system of information-measuring devices were presented. Simulation of the synthesized controller was carried out. The simulation results were represented. The research results are of interest of the field of the wide class information-measuring devices such as the direction-finding devices, the optical sensors, and the observation equipment.